Intravenous superoxide dismutase as a protective agent to prevent impairment of lung function induced by high tidal volume ventilation - Nan-Chun Wu; Fan-Ting Liao; Hao-min Cheng; Shih-Hsien Sung; Yu-Chun Yang; Jiun-Jr Wang (BMC Pulmonary Medicine, 2017)
Abstract Background Positive-pressure mechanical ventilation is essential in assisting patients with respiratory failure in the intensive care unit and facilitating oxygenation in the operating room. However, it was also recognized as a primary factor leading to hospital-acquired pulmonary dysfunction, in which pulmonary oxidative stress and lung inflammation had been known to play important roles. Cu/Zn superoxide dismutase (SOD) is an important antioxidant, and possesses anti-inflammatory capacity. In this study, we aimed to study the efficacy of Cu/Zn SOD, administered intravenously during high tidal volume (HTV) ventilation, to prevent impairment of lung function. Methods Thirty-eight male Sprague-Dawley rats were divided into 3 groups: 5 h ventilation with (A) low tidal volume (LTV; 8 mL/kg; n = 10), (B) high tidal volume (HTV; 18 mL/kg; n = 14), or (C) HTV and intravenous treatment of Cu/Zn SOD at a dose of 1000 U/kg/h (HTV + SOD; n = 14). Lung function was evaluated both at baseline and after 5-h ventilation. Lung injury was assessed by histological examination, lung water and protein contents in the bronchoalveolar lavage fluid (BALF). Pulmonary oxidative stress was examined by concentrations of methylguanidine (MG) and malondialdehyde (MDA) in BALF, and antioxidative activity by protein expression of glutathione peroxidase-1 (GPx-1) in the lung. Severity of lung inflammation was evaluated by white blood cell and differential count in BALF, and protein expression of inducible nitric oxide synthase (iNOS), intercellular adhesion molecule-1 (ICAM-1), tumor necrosis factor-α (TNF-α), matrix metalloproteinase-9 (MMP-9), and mRNA expression of nuclear factor-κB (NF-κB) in the lung. We also examined protein expression of surfactant protein (SP)-A and D and we measured hourly changes in serum nitric oxide (NO) level. Results Five hours of LTV ventilation did not induce a major change in lung function, whereas 5 h of HTV ventilation induced apparent combined restrictive and obstructive lung disorder, together with increased pulmonary oxidative stress, decreased anti-oxidative activity and increased lung inflammation (P < 0.05). HTV ventilation also decreased SP-A and SP-D expression and suppressed serum NO level during the time course of ventilation. Cu/Zn SOD administered intravenously during HTV ventilation effectively reversed associated pulmonary oxidative stress and lung inflammation (P < 0.05); moreover, it preserved SP-A and SP-D expressions in the lung and increased serum nitric oxide (NO) level, enhancing vascular NO bioavailability. Conclusions HTV ventilation can induce combined restrictive and obstructive lung disorders. Intravenous administration of Cu/Zn SOD during HTV ventilation can prevent lung function impairment and lung injury via reducing pulmonary oxidative stress and lung inflammation, preserving pulmonary surfactant expression, and enhancing vascular NO bioavailability.